Enriching distinctive microbial communities from marine sediments via an electrochemical-sulfide-oxidizing process on carbon electrodes - Li, Shiue-Lin; Nealson, Kenneth H. (Frontiers in Microbiology, 2015)
Sulfide is a common product of marine anaerobic respiration, and a potent reactant biologically and geochemically. Here we demonstrate the impact on microbial communities with the removal of sulfide via electrochemical methods. The use of differential pulse voltammetry revealed that the oxidation of soluble sulfide was seen at + mV (vs. SHE) at all pH ranges tested (from pH = 4 to 8), while non-ionized sulfide, which dominated at pH = 4 was poorly oxidized via this process. Two mixed cultures (CAT and LA) were enriched from two different marine sediments (from Catalina Island, CAT; from the Port of Los Angeles, LA) in serum bottles using a seawater medium supplemented with lactate, sulfate, and yeast extract, to obtain abundant biomass. Both CAT and LA cultures were inoculated in electrochemical cells (using yeast-extract-free seawater medium as an electrolyte) equipped with carbon-felt electrodes. In both cases, when potentials of +630 or 130 mV (vs. SHE) were applied, currents were consistently higher at +630 then at 0 mV, indicating more sulfide being oxidized at the higher potential. In addition, higher organic-acid and sulfate conversion rates were found at +630 mV with CAT, while no significant differences were found with LA at different potentials. The results of microbial-community analyses revealed a decrease in diversity for both CAT and LA after electrochemical incubation. In addition, some bacteria (e.g., Clostridium and Arcobacter) not well known to be capable of extracellular electron transfer, were found to be dominant in the electrochemical cells. Thus, even though the different mixed cultures have different tolerances for sulfide, electrochemical-sulfide removal can lead to major population changes.